Internal Medicine Clerkship Team-Based Learning Series: Chest Pain Module - Steven Bishop; Jeffrey Kushinka; Stephanie Call (Association of American Medical Colleges, 2012)
Abstract This team-based learning (TBL) module on chest pain is designed to complement a clerkship in internal medicine for third-year medical students. It focuses on the common causes of chest pain, developing the differential diagnosis of chest pain, and the initial evaluation and treatment of patients with common chest pain syndromes. The resource includes learning objectives specific to the chest pain module, as well as the individual readiness assurance test (iRAT), group readiness assurance test (gRAT), and group application exercises (with correct answers bolded and answer explanations). An instructor's guide is also included and gives a detailed overview of how to go about implementing the module and where to find more information about TBL if the instructor is using this method for the first time. This module is one of eight in a series. Other modules address the following internal medicine topics: anemia, dyspnea, altered mental status, back pain, joint pain, abdominal pain, and acid-base disorders. Each module is designed to take approximately 90 minutes to complete. The modules may be completed in any order by the instructor and do not need to be done sequentially. Each module is an independent topic and does not require knowledge from the other modules in order to be completed by the students. As such, they may be used alone or in any desired combination suitable to the instructor's needs. However, we found that utilizing all eight modules over the course of a clerkship period is a comprehensive method of covering the core topic areas and reinforces knowledge attained by other educational methods during the clerkship (e.g., clinical experiences, traditional lecture, independent study, etc.). Additionally, the modules could also be easily adapted for use by physician assistant and nurse practitioner programs.